Study on Transports of Atmospheric Pollutants under Global Wind by Dynamical System Approach - Wang, Wei; Zhang, Jiazhong; Li, Zhihui; Wang, Chunxue; Wang, Dalei (Journal of Environmental Accounting and Management, 2026)
The transport of atmospheric pollutants under global wind is analyzed from viewpoint of dynamical system, with the Lagrangian coherent structures (LCSs) extracted from the wind field. First, the distribution of global atmospheric pollutants is presented using the data of inhalable particulate matters and dust aerosols. Then, the transports of pollutants are analyzed using hyperbolic LCSs extracted from the global wind field, with a detailed analysis of the North Atlantic region. Finally, the formation and evolution of vortices in the process of pollutants transport are analyzed further by Lagrangian-averaged vorticity deviation (LAVD) method. It can be concluded that the transport of pollutants is closely related to the hyperbolic LCSs in the wind field. Importantly, these structures as transport barriers can act as the transport channels of particulate matters, and one conceptual design to control atmospheric pollutants efficiently could be provided tentatively, based on studies presented.